Effectiveness of fungicidal seed treatments applied to smooth or shrivelled soybean seeds contaminated by Diaporthe phaseolorum - Hall, R.; Xue, A.G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
The effect of 11 fungicides on six lots of soybean (Glycine max) seed produced in Ontario in 1986-1987 and contaminated with Diaporthe phaseolorum var. caulivora (7-76%) and D. phaseolorum var. sojae (5-19%) was examined. Phomopsis longicolla also contaminated three of these seed lots at low rates (1-2%). The fungicide Vitaflo-280®, a mix of carbathiin and thiram, increased soybean seedling emergence, plant stand at harvest and seed yield, and decreased the severity of stem infection when applied to three lots of discolored and shrivelled seed, but was ineffective when applied to three lots of bright and smooth seed. The effectiveness of this product was not related to the incidence of contaminated seed. A further 10 fungicidal products were similarly effective and ineffective when applied to shrivelled and smooth seed lots, respectively. The most effective active ingredients were thiram, carbathiin, benomyl and captan, and the most effective commercial products available in Ontario were Vitaflo-280®, Vitavax P®, Thiram 320F®, and Anchor®. The maximum increase in seed yield was 60.5%.